Market Concentration and Firm Performance : Evidences from the Indian Life Insurance Industry - Chakraborty, Joy (Indian Journal of Finance, 2016)
In the pre-reform era, Life Insurance Corporation of India (LICI) dominated the Indian life insurance sector with a market share of close to 100%. But the situation drastically changed since the beginning of the year 2000. With the development of the Insurance Regulatory and Development Authority of India (IRDAI) Act in 1999, private players started entering into the Indian life insurance market. At the end of the FY 2014-15, the market share of LICI stood at 73.48% with the number of private players having risen to 23 in the country's life insurance sector. One of the reasons for such a decline in the market share of LICI during the post-reform period could be attributed to the increasing competition from the private players in the country's life insurance sector. The present study attempted to evaluate the extent of concentration and competition prevailing in the Indian life insurance market over the study-period from 2008-09 to 2014-15, against the backdrop of the global financial crisis. In addition, an attempt was made to ascertain any significant differences in the performances of the 18 life insurance companies in India, inclusive of LICI, in terms of life insurance premium underwritten during the period under review. The present study revealed the pre-existing dominance of LICI in the Indian life insurance market, both in terms of market concentration and premiums underwritten, even after 15 years since the privatization of the country's insurance sector.